2018
DOI: 10.17675/2305-6894-2018-7-3-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of triazoloazepine bromide with biocidal activity on microbial copper corrosion

Abstract: The study deals with the effect of triazoloazepine bromide with biocidal activity against sulfate-reducing bacteria on microbial copper corrosion in neutral water-salt Postgate "B" medium with the enrichment culture of bacteria, isolated from the biofilm, formed on the metal surfaces of sewage treatment facilities. It has been established that the studied substance also inhibits the growth of iron-reducing bacteria, denitrifying bacteria and ammonifying bacteria, which ensure the stable growth of the most nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…H. Hlushko et al described synthetic polymeric antioxidants as powerful inhibitors of corrosion of metals [94,95]. Hydrophobic synthetic antioxidant copolymers, containing catechol or gallol moieties, can be used as single layer individual coatings or as additives to epoxy-based coatings for protection of AA2024 substrates.…”
Section: Determination Of the Anticorrosion And Antioxidant Propertiementioning
confidence: 99%
“…H. Hlushko et al described synthetic polymeric antioxidants as powerful inhibitors of corrosion of metals [94,95]. Hydrophobic synthetic antioxidant copolymers, containing catechol or gallol moieties, can be used as single layer individual coatings or as additives to epoxy-based coatings for protection of AA2024 substrates.…”
Section: Determination Of the Anticorrosion And Antioxidant Propertiementioning
confidence: 99%
“…Triazoloazepinium bromide (TAB) has been known to inhibit growth activity of SRB, IRB, denitrifying bacteria, and ammonifying bacteria ( Kurmakova et al, 2018 ). In their recently published work, Kurmakova et al (2018) showed that TAB inhibited the sulfate-reducing activity of bacteria by increasing the redox potential of the corrosive medium by up to 170 mV. The authors proposed that TAB adsorbs on copper by transferring electrons from negative ions present in its molecule, to the unoccupied metal orbitals.…”
Section: Recent Developments In Inhibition Of Copper Microbiologicall...mentioning
confidence: 99%